Electrochemical Determination of Salivary N‐Acetylneuraminic Acid by Miniaturized Capillary Electrophoresis Coupled with Sample Stacking. Issue 9 (10th August 2016) - Zheng, Yiliang; Wang, Tingting; Kong, Jiaxing; Ma, Yaolu; Heng, Yi; Ren, Yujuan; Ye, Jiannong; Chu, Qingcui
Abstract: Due to their important biological role as markers for different pathologies, sialic acid (SA) analyses are important for clinical research. In this work, a miniaturized capillary electrophoresis with amperometric detection (mini‐CE‐AD) was developed for the determination of N ‐acetylneuraminic acid (NANA), which is the most widespread form of SAs. NANA was first oxidized by periodic acid in an acidic solution, and then the oxidation product β ‐formyl pyruvic acid was derivatized with electroactive 2‐thiobarbituric acid (TBA) to form an electroactive NANA‐TBA adduct, which could be readily determined by mini‐CE‐AD. The limit of detection (LOD) of NANA‐TBA could achieve 0.50 µg/mL (1.6 µmol·L −1, S/N=3) based on an online enrichment approach of moving chemical reaction boundary. The proposed method was successfully applied to the analysis of NANA in human saliva, and the recoveries were in the range of 91.8% –109% with RSDs of 1.8% –3.9%. Due to its simple design and construction, low cost and portability, the mini‐CE‐AD device will possess more practicability in more field work as an alternative to conventional and microchip CE approaches. Abstract : A miniaturized capillary electrophoresis with amperometric detection (mini‐CE‐AD) was developed for the determination of N ‐acetylneuraminic acid (NANA), and 2‐thiobarbituric acid (TBA) was used as an electrochemical derivation agent. The limit of detection could achieve 0.50 µg/mL (1.6 µmol·L −1, S/N=3) based on an online enrichment approach of moving chemical reaction boundary. The proposed method was successfully applied to the analysis of NANA in human saliva. Due to its simple design and construction, low cost, and portability, the mini‐CE‐AD device should possess more practicability in more field work as an alternative to conventional and microchip CE approaches.